2019
DOI: 10.1111/jfd.13050
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of potential vertical transmission of tilapia lake virus

Abstract: Tilapia lake virus disease (TiLVD) is an emerging viral disease in tilapia with worldwide distribution. Although the horizontal transmission of TiLV has been demonstrated through the cohabitation of infected fish with susceptible fish, no direct experiment showed the potential of vertical transmission from broodstock to progeny. In this study, natural outbreaks of TiLV in broodstock and fry in two tilapia hatcheries were confirmed. The TiLV genomic RNA was detected in liver and reproductive organs of infected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 20 publications
2
36
0
Order By: Relevance
“…Warnings about the risk of the transboundary spread of the virus across borders as a result of vertical transmission were reported in early 2017 following the detection of the virus in fertilized eggs, fry and fingerlings in tilapia hatcheries (Dong, Ataguba, et al, 2017). Further evidence supported this potential vertical route of transmission (Yamkasem, Tattiyapong, Kamlangdee, & Surachetpong, 2019). Our results showed the presence of TiLV in asymptomatic broodstock from several Bangladeshi tilapia hatcheries.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Warnings about the risk of the transboundary spread of the virus across borders as a result of vertical transmission were reported in early 2017 following the detection of the virus in fertilized eggs, fry and fingerlings in tilapia hatcheries (Dong, Ataguba, et al, 2017). Further evidence supported this potential vertical route of transmission (Yamkasem, Tattiyapong, Kamlangdee, & Surachetpong, 2019). Our results showed the presence of TiLV in asymptomatic broodstock from several Bangladeshi tilapia hatcheries.…”
Section: Discussionmentioning
confidence: 82%
“…As further support for this hypothesis, it was found that the virus infected the reproductive organs of these fish and was then passed on to the fertilized eggs (Dong et al., 2020). All these findings point towards strict recommendation to avoid, at all costs, the use of TiLV‐infected broodstock for production of tilapia fry (Dong et al., 2020; Yamkasem et al., 2019). Therefore, we strongly urge that immediate actions should be taken by the relevant authorities and various aquaculture stakeholders to develop systematic testing protocols and a certification system for tilapia hatcheries, as well as the implementation of proper biosecurity to ensure that tilapia fingerlings are produced from reliable sources of TiLV‐negative broodstock.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of TiLV, horizontal transmission may occur when healthy stocks come into contact with diseased individuals (Eyngor et al, 2014;Jansen et al, 2018). Recently, vertical transmission of TiLV has also been proposed (Yamkasem, Tattiyapong, Kamlangdee, & Surachetpong, 2019).…”
Section: Re Sults and Discussionmentioning
confidence: 99%
“…Moreover, it is worthwhile to investigate further whether SDDV invades the reproductive organs of Asian sea bass broodfish and could vertically transmit to the offspring as occurred in the case of tilapia lake virus (TiLV), a newly emerging virus of tilapia (Dong et al, 2020; Yamkasem et al, 2019). Understanding the route of disease transmission in combination with highly sensitive detection method is vital for effective disease management and preventing potential widespread.…”
Section: Discussionmentioning
confidence: 99%